THE INFLUENCE OF ACTIVATED ZEOLITE ON THE DECREASING OF NH3 CONCENTRATION IN FISH POND WATER - Daman Suyadi; M. Ulum A. Gani (Indonesian Mining Journal, 2008)
A research on the utilization of zeolite from Tadisi Village, Sumarorang, Polmas, West Sulawesi had been carried out. The objective of this research is to identify the influence of activated zeolite both physically and chemically on the decreasing of NH3 concentration in fish pond water. The physical activation in this research was done by heating of zeolite samples at the temperature of 100, 200 and 300°C , while the chemical activation was carried out by using reagent of NaOH with the concentration of 2 N. The particle size of the zeolite used in this research was – 4 + 10 mesh and the weight of activated zeolite samples put into the fish pond water samples were 1; 5; and 10 grams with contact time of 0, 1, and 5 days, respectively. The optimal result of this research indicated that by the addition of 5 grams of the activated zeolite (which had been activated at the temperature of 300°C with contact time for one day), the NH3 concen- tration of fish pond water samples decreased as much as 54.97 %. The addition 10 grams of the activated zeolite (which had been activated by NaOH with concentration of 2 N with contact time for five days showed the optimum result by decreasing of the NH3 concentration in fish pond water samples as much as 45.01 %.